The Effectiveness of Digital Comic Media to Increase Zakat and Waqf Literacy in Generation Z - Haqiqi, Ahmad Zaki; Amelia, Erika (International Journal of Zakat, 2025)
The declining levels of zakat and waqf literacy among Generation Z pose a challenge to the development of Islamic philanthropy in Indonesia. Conventional educational methods have not been effective in enhancing this generation's understanding of zakat and waqf concepts. Therefore, research is needed to analyze the effectiveness of using digital comics as a strategy to increase zakat and waqf literacy among Generation Z. This study aims to measure the improvement in Generation Z's understanding of zakat and waqf after exposure to digital comics, as well as evaluate the effectiveness of this medium as a learning tool. The research employs an experimental method with pre-test and post-test, involving a sample of 96 Generation Z respondents. The results show a significant increase occurred in zakat and waqf literacy scores, with an average increase of 35.2% from pre-test to post-test. A total of 91.67% of respondents experienced an increase in scores; this finding implies that digital comics have the potential to be an effective medium. However, this finding must be interpreted with caution given the single-group research design used and the measurement focusing only on short-term retention. Further analysis reveals that digital comics are effective in presenting complex information, aligning with Generation Z's preferences, and enhancing learning enthusiasm. This study also demonstrates that the use of digital comics successfully narrows the comprehension gap among respondents, reflecting flexibility towards various initial levels of understanding and different learning styles.